The association between the dietary index for gut microbiota and its components with cardiovascular disease risk: a cross-sectional study based on NHANES - Na, Lin; Chang, Jing; Li, Xinqi; Che, Xiaona; Sun, Yunfei; Cui, Wenjing; Xue, Xin (Frontiers in Nutrition, 2025)
IntroductionCardiovascular disease (CVD) is a leading cause of mortality worldwide, and its development and progression are closely associated with diet-induced changes in gut microbiota. This study aims to investigate the relationship between the dietary index for gut microbiota (DI-GM) and its components, including the beneficial gut microbiota score (BGMS) and the unfavorable gut microbiota score (UGMS), in relation to cardiovascular disease.MethodsWe conducted a cross-sectional study using National Health and Nutrition Examination Survey (NHANES) data (1999–2020), collecting baseline sociodemographic and health-related data from 41,193 adults aged ≥20 years. We constructed multivariable weighted logistic regression models to evaluate associations between DI-GM, BGMS, UGMS, and CVD risk, generating weighted restricted cubic spline (RCS) plots to visualize dose–response relationships. Subgroup analyses assessed outcome robustness across sex, age, hypertension, and diabetes subgroups.ResultsAfter adjusting for confounders (age, sex, race, poverty-to-income ratio [PIR index], marital status, and education level, smoking status, alcohol consumption, body mass index [BMI], and comorbidities), significant associations emerged between DI-GM, BGMS, and CVD risk. Increasing DI-GM and BGMS levels showed gradually decreasing CVD risk trends (DI-GM: OR = 0.97, 95% CI: 0.94–1.00, p < 0.05; BGMS: OR = 0.92, 95% CI: 0.88–0.96, p < 0.05). No significant association was found between UGMS and CVD risk (OR = 1.04, 95% CI: 0.99–1.08, p > 0.05). Subgroup analyses revealed more significant DI-GM and BGMS associations with CVD risk in female versus male participants (p for interaction < 0.05).ConclusionAmong adults aged ≥20 years, DI-GM and BGMS showed significant inverse association with CVD risk. Compared to DI-GM, BGMS demonstrates a stronger inverse association with cardiovascular disease risk. These findings underscore the potential crucial role of favorable dietary patterns in cardiovascular disease prevention.